2012
DOI: 10.1016/j.jacc.2012.02.066
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Catecholaminergic Polymorphic Ventricular Tachycardia With Patient-Specific Human-Induced Pluripotent Stem Cells

Abstract: This study highlights the potential of hiPSCs for studying inherited arrhythmogenic syndromes, in general, and CPVT specifically. As such, it represents a promising paradigm to study disease mechanisms, optimize patient care, and aid in the development of new therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
148
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 200 publications
(161 citation statements)
references
References 27 publications
13
148
0
Order By: Relevance
“…7,8 In the cardiac field, hiPSCs were established from healthy individuals and from patients inflicted with acquired 9 and several types of inherited cardiac disorders. 10,11 Patient-specific hiPSC-derived cardiomyocyte (hiPSC-CM) models of different inherited arrhythmogenic syndromes (including the long-QT, [12][13][14][15] Brugada, 16 and sodium channel overlap 17 syndromes; arrhythmogenic right ventricular cardiomyopathy 18,19 ; and both types of CPVT [20][21][22][23][24][25][26][27][28][29] ) were…”
Section: See Editorial By LI Et Almentioning
confidence: 99%
“…7,8 In the cardiac field, hiPSCs were established from healthy individuals and from patients inflicted with acquired 9 and several types of inherited cardiac disorders. 10,11 Patient-specific hiPSC-derived cardiomyocyte (hiPSC-CM) models of different inherited arrhythmogenic syndromes (including the long-QT, [12][13][14][15] Brugada, 16 and sodium channel overlap 17 syndromes; arrhythmogenic right ventricular cardiomyopathy 18,19 ; and both types of CPVT [20][21][22][23][24][25][26][27][28][29] ) were…”
Section: See Editorial By LI Et Almentioning
confidence: 99%
“…15 In the current study, we aimed to use the emerging hiPSC technology to establish an in vitro model of ARVC. We Background-Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a primary heart muscle disorder resulting from desmosomal protein mutations.…”
mentioning
confidence: 99%
“…Electrophysiological analysis of these cells revealed a heterogeneous population comprising cells with nodal, atrial, and ventricular profiles (data not shown, Priori, S.G., et al, J. Clin. Invest., In Press, 14,15,20 ). …”
Section: Representative Resultsmentioning
confidence: 99%